Growth of 300-nm-thick epitaxial AlInN films on a semi-relaxed c-plane GaInN template by metalorganic chemical vapor deposition. (17th February 2021) - Miyoshi, Makoto; Yamanaka, Mizuki; Egawa, Takashi; Okada, Narihito; Tadatomo, Kazuyuki; Takeuchi, Tetsuya
Abstract: Metalorganic chemical vapor deposition of approximately 300-nm thick epitaxial AlInN films with different alloy compositions was performed using a semi-relaxed c -plane GaInN template as an underlying substrate. The GaInN template consisted of a Ga0.98 In0.02 N film on a facet-structured GaN film formed on a c -plane sapphire substrate by the epitaxial lateral overgrowth technique, and its surface was treated with the chemical-mechanical polishing. It was observed that an Al0.835 In0.165 N film grown with an in-plane tensile strain exhibited a relatively smooth surface whereas an Al0.781 In0.219 N film grown with an in-plane compressive strain exhibited a granular morphology owing to a columnar polycrystalline structure. This phenomenon was quite similar to that observed for AlInN films grown non GaN/sapphire templates (GaN templates); therefore, it was speculated that the microstructure variation might have been caused by the in-plane compressive strain generated in AlInN films on the GaInN template in the same way as on GaN templates or FS-GaN substrates.